Kajian Tentang Substitusi Talas Sebagai Bahan Dasar Dalam Produksi Terhadap Kualitas Es Krim - Candra Kusuma Wijaya; Sunyoto Sunyoto; Setiyo Budiharjo (Jurnal Pariwisata Indonesia, 2021)
Taro is a food staple that has rich benefits and is easy to use as a food processing product. Taro with white flesh is often used as a basic ingredient for delicious and nutritious staples, one of which is taro ice cream. This study aims 1. To determine the flow of the processing process for taro substitution for ice cream filling. 2. Knowing the effect of using taro substitutes for ice cream fillers on the quality of the ice cream produced. The type of research used in the manufacture of this product is an experiment with a product development model. The results obtained in this study are: 1. The processing of taro by means of a fine blender and then put it into the ice cream mixture. 2. The effect of taro substitution on ice cream fillers is: color: pink, aroma: powdered milk, taste: sweet, texture: soft. So that the use of taro substitution affects the quality of the ice cream. 1. So the effect of taro substitution on ice cream has a good impact on society. 2. Ice cream with taro substitution influences in terms of taste, aroma, texture, and color.